Analysis of design and implementation of physical education curriculum in primary school: A literature study - Pinton Setya Mustafa; Wawan Sundawan Suherman; Sumarjo Sumarjo; Dewi Nurhidayah; Luthfie Lufthansa; Tama Anugrah (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Physical education is a vital component of the primary school curriculum, aiming to develop students' physical skills, health, and psychosocial well-being. Various approaches have been implemented to achieve these goals, including curriculum integration and addressing the challenges within the primary school curriculum. This study aims to systematically analyze the design and implementation of physical education curriculum in primary schools by reviewing 20 research articles, with a focus on identifying practices and challenges encountered. The methodology used follows a systematic review guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Relevant research articles were identified through a Scopus database search using specific keywords, followed by predefined inclusion and exclusion criteria. The analysis results indicate that physical education curriculum approaches are diverse, including health-based and mindfulness curricula, ecological dynamics approaches, alternative curricula, and integration with specific models or policy foundations, all aiming to have a positive impact on the physical, cognitive, social, and emotional development of primary school students by incorporating biomechanical concepts, conflict management strategies, integration of thinking skills, and motor skill development. Additionally, teacher preferences regarding the implementation of physical education curricula were also found. This review concludes that various approaches to implementing physical education curricula positively affect student development. The findings highlight that an effective primary school physical education curriculum should integrate a holistic approach involving physical, cognitive, social, and emotional aspects. The importance of flexibility in the curriculum, allowing adaptation to local and individual student needs, is also acknowledged.